Simulation Of Reactive Distillation Column Of Methyl Tert- Butyl Ether Production - Shanmugasundaram, Parrathen (Universiti Sains Malaysia, 2021)
Reactive distillation is an efficient technique of combination of both reaction and separation in a single unit beneficial for equilibrium-limited reactions, cost-effective , reduce energy and improvement purity of the product. The usage of reactive distillation column has increased attention because of its high potential for process intensification and therefore this process needs to be studied fully so that the reaction conversion and purity of the product are assured before its implementation in industrial scale. In this work, Aspen Plus was used for simulation of reactive distillation column where methanol and butene undergo esterification reaction to produce Methyl tert-butyl ether (MTBE) and undergo continuous separation process. Firstly, the results are compared for both literature and simulation studies. The simulated results obtained by Aspen Plus showed that it is acceptable range since the simulation values obeyed that of the literature with a purity errors of top and bottom for MTBE is 0.0048% and 0.0026% respectively. In addiction, simulation results have been performed for sensitivity analysis. Sensitivity analysis on the same RadFrac model showed that reflux ratio of 7, number of reactive stages at 10, and reboiler of 11.45 have significant effects on met MTBE purity. Sensitivity analysis conducted shows that the MTBE purity were maximum at reflux ratio 7. The best feed location for butene at stage 3 while methanol feed at stage 12.